Globalization and the Transformation of Foreign Economic Policy. - Bozyk, Pawel (Transition and development., 2007)
This volume charts the journey from the point when foreign economic policy was solely concerned with foreign trade to the current globalization of the world economy that creates a uniform market in goods, services and factors of production that embrace all countries and regions. It traces the goals and instruments of foreign economic policy during this period, providing insight into the long-run trends and developing new theoretical generalizations.